Performance evaluation of three encryption/decryption algorithms - Kofahi, N.A.; Turki Al-Somani; Khalid Al-Zamil (2003 46th Midwest Symposium on Circuits and Systems, 2003)
This paper presents an implementation of three encryption algorithms and a comparison between them based on CPU execution time. The CPU execution time is broken down to kernel and user time. The selected algorithms are: DES, Triple-DES (T-DES) and Blowfish. These are symmetric block encryption algorithms. The objective of this research is to evaluate the performance of the three cryptography algorithms in terms of the processing time required in the kernel and user space for generating the secret key, encryption and decryption operations. The powerful portable programming language Java and JCA (Java cryptography architecture) is used in implementing the encryption algorithms. The performance of the implemented encryption algorithms will be evaluated on SunOS platforms. The results show that the Blowfish algorithm is the fastest, followed by the DES algorithm then the T-DES algorithm